A comparative analysis of the protection of women's labour rights in the apparel industries of the Southern African Customs Union member states of South Africa and Lesotho, under the African Growth and Opportunity Act. - Molapo, Tšoarelo (Department of Commercial Law, 2014)
Includes bibliographical references.